ANALISIS KESULITAN BELAJAR SISWA DALAM MEMAHAMI MATERI PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP KELAS XII MIPA SMAN 1 CIBUNGBULANG KABUPATEN BOGOR - Lina Widiastuti (FKIP UNIVERSITAS PAKUAN, 2020)
ANALYSIS OF STUDENT’S LEARNING DIFFICULTIES IN UNDERSTANDING THE MATERIAL GROWTH AND DEVELOPMENT OF LIVING THINGS CLASS XII MIPA SMAN 1 CIBUNGBULANG BOGOR DISTRICThis study aims to obtain information about students' learning difficulties on the material for the growth and development of living things that are studied in odd semester XII Mathematics and Natural Sciences and what factors are causing them. The method used in this research is descriptive method. The population in this study were all students of class XII MIPA in SMA Negeri 1 Cibungbulang in the academic year 2019/2020 with a sample of one class, namely class XII MIPA 1, amounting to 36 people consisting of 26 female students and 10 male students. Data in the form of student learning outcomes were collected using a description test instrument, amounting to 9 questions, while data regarding student responses to biology subjects and data to explore the factors causing student learning difficulties using a questionnaire or questionnaire. Data analysis using the description test found that 26 students out of 36 students achieved grades below the KKM which meant that 72% of students had learning difficulties. Based on the results of this study it can be concluded that 72% of students have difficulty learning in understanding the material for growth and development in living things. The most difficulty level of students is in the medium category (38.9%) followed by the low (25%) and high categories (25%) i. Only 11, 1% of students in the very low learning disability category. Student interest, student attitudes, student health, family support, completeness of facilities and infrastructure of teaching methods and the general condition of the student's home environment already support the learning process and are not factors in causing learning difficulties experienced by students. Factors that cause students 'learning difficulties turned out to be due to the test questions which according to students were difficult to do because 55.5% of the questions included analytical questions (HOTS) so that students' test scores were relatively low on growth and development material in living things.